Efektivitas Model Peningkatan Kompetensi Profesional Guru Biologi Berbasis Continuous Professional Development (CPD) di Karesidenan Surakarta - Sofyan Anif; Almuntaqo Zain (Jurnal VARIDIKA, 2015)
The  Indonesian  Law  No.  14  Year  2005  on  teacher  and  lecturer  and Government Regulation No 74 Year 2008 on teacher, have mandated the government to carry out certiﬁ cation for teachers of all subjects who have met the requirements. Based on a survey conducted by the Directorate General of Quality Improvement of Teachers and Education Personnel  (PMPTK) in 2009, the certiﬁ cation program has not been able to improve the competence and professionalism of teachers signiﬁ cantly so it has not given positive inﬂ uence on improving the performance of teachers. The purpose of this study is to determine the effectiveness of the model of professional competence  improvement  of  biology  teacher  based  on  initial  competence  test  in Surakarta.This research uses R D approach developed by Borg and Gall (2007), which includes six procedures or stages of development: (1) determine the product; (2) conduct a theoretical and empirical study; (3) development planning; (4) the development of early models; (5) validation of the model; and (6) the discovery of the ﬁ nal product. The ﬁ rst up to the fourth stage has been done in previous studies, and this research is  the  ﬁ fth  stage  namely  the  stage  of  model  validation  through  limited  experiment with  one-group  pretest-Posttest  Design.  While  the  data  analysis  uses  traditional descriptive quantitative approach.The results of the study on the effectiveness of implementation of the model of increasing Biology  teacher  competence  based  on  CPD  on  a  limited  scale  test  show  that  the classical absorption of pretest is 27.78%, while the classical absorption of post-test is 72.22%. It means that Biology teacher competence based on CPD has increased in a limited test scale of 44.44%. The results of a statistical analysis of the increase of pre- test and post-test absorption on each competence shows that the greatest increase of percentage in absorption was on the competence: “understanding the concepts, laws, and theories of biology and ﬂ exible implementation” for 38.89%. While the lowest increase of percentage in the absorption occurred on the competence: “conducting action research to increase professionalism” with only 13.27%.